Simplified engineering for architects and builders - Ambrose, James E.; Tripeny, Patrick (Hoboken, NJ : John Wiley & Sons, 2011)
'Major revision of this classic reference is reorganized and updated to reflect the latest practices in the design of structures. Since 1938, Simplified Engineering for Architect and Builders has endured as the reference of choice for designers and constructors who need to know the practical procedures for the design of commonly used structures for buildings. Covering both the LRFD and ASD methods for structural design, Simplified Engineering is the go-to book for those working on the design of steel, wood, concrete and masonry building structures'--
Includes bibliographical references and index.
Keywords: Structural engineering